2021
DOI: 10.1111/jog.14707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of critical miRNAs and mRNAs associated with polycystic ovary syndrome

Abstract: Aim Polycystic ovary syndrome (PCOS) is a complicated endocrine and metabolic abnormality diseases common in women of child‐bearing age. This study aims to screen out critical miRNAs and mRNAs associated with PCOS, which may be conducive to offer novel insights and treatment for the diseases. Methods Three mRNA datasets and one miRNA dataset derived from granulosa cells of patients with PCOS and normal controls were downloaded to obtain the differentially expressed mRNAs (DEmRNAs) and miRNAs (DEmiRNAs). Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The results showed that at the second and fourth weeks after induction, the calibrated concentration of undiluted samples in the D-galactose group was meaningfully higher than that of rat normal samples. According to a different bioinformatics study, PCOS has a significantly enriched D-galactose metabolism pathology [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that at the second and fourth weeks after induction, the calibrated concentration of undiluted samples in the D-galactose group was meaningfully higher than that of rat normal samples. According to a different bioinformatics study, PCOS has a significantly enriched D-galactose metabolism pathology [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can also impede oocyte growth and decrease the bioactivity of FSH. D-galactose metabolism is a disease that is greatly enriched in PCOS, which is relevant to the relationship between D-galactose and PCOS [ 11 ]. The pathogenic mechanisms in premature ovarian failure include the generation of anti-ovarian antibodies (AOA) against ovarian antigens, infiltration of inflammatory cells, elevated levels of proinflammatory cytokines, and decreased Tregs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… 23 Another bioinformatics analysis has suggested that galactose metabolism is a significantly enriched pathway in PCOS. 24 To date, no study has investigated the circulating galactose levels in patients with PCOS. Our results clearly indicate higher baseline galactose levels in women with PCOS, which are correlated with PCOS itself, and independent of the metabolic status as well as other relevant covariates.…”
Section: Discussionmentioning
confidence: 99%